Pengaruh Ukuran Perusahaan, Profitabilitas, Struktur Modal, Kebijakan Deviden Terhadap Nilai Perusahaan (Sudi pada Perusahaan Makanan dan Minuman yang terdaftar di BEI periode 2018-2020) - Tri Cahyo Nugroho; Rizka Mukhlisiah; Eduard Hotman Purba (IJAcc, 2022)
This study aims to examine the effect of firm size, profitability, capital structure and dividend policy on firm value. The statistical method used is multiple regression analysis. The type of data used in this study is secondary data whose data source is obtained from the Indonesia Stock Exchange for the 2018-2020 period. The population in this study are companies engaged in the food and beverage sector listed on the Indonesia Stock Exchange for the period 2018 - 2020 as many as 22 companies. The sampling technique was purposive sampling method. The results of this study indicate that firm size, profitability, capital structure have no effect on firm value, while liquidity has no effect on firm value